Inclusive reactions of stripping and fragmentation involving light cluster nuclei at intermediate energies - V. I. Kovalchuk (Ядерна фізика та енергетика)
In the framework of eiconal approximation and the double folding model, a formalism for calculating inclusive spectra of particles from stripping and fragmentation reactions involving light cluster nuclei is proposed. The cross-section of the 12C(3He, d)13N reaction at an incident particle energy of 81.4 MeV and the proton spectra from the deuteron fragmentation reaction with 56 MeV energies by 12C and 27Al nuclei are described. The calculated values satisfactorily fit the corresponding experimental data.